Meningiomas of the Pediatric Skull Base: A Review - Gump, William C. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Pediatric skull base meningiomas are rare and complex clinical entities. Meningioma is a relatively uncommon brain tumor in children, and only ∼ 27% involve the skull base. Some evidence suggests that these tumors are more likely to be atypical or malignant in children than adults. The absence of female preponderance in pediatric meningiomas is reflected in the skull base subpopulation. Skull base meningiomas in children are most likely to be found in the anterior or middle fossa base, or involving the orbit and optic nerve sheath. Petroclival, suprasellar/parasellar, cerebellopontine angle, cavernous sinus, and foramen magnum tumors are very rare. Meningiomas constitute a small proportion of reported cases of pediatric skull base pathology, and they are entirely absent from many case series. Initial gross total resection is consistently associated with superior outcomes. Surgical approaches to the pediatric skull base must take additional factors into consideration including relatively smaller anatomy, immature dentition, incompletely aerated sinuses and air cells, and altered configurations of structures such as the pterional bony complex. Multidisciplinary expertise is essential to optimizing treatment outcomes.
Keywords: meningioma; pediatric skull base; review